(3JPcQI GHf eJhjI aj CMcGe GdLhGgQ hGdCYQGVs - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj,J (B468 (3g` s
(3ChdgG (B:s
(3gPg JPcQI JTJed Ydi HjGf CMcGe GdeYdheGJ hChUGagG hjLeY Edi GdEjLGR ai Gdbhd s
(3BNQgG (B:s
(3hCeG GdQLd agh Je GdcJGH Hef Gddg hJhajbg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B26 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B692s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds